KAJIAN MANAJEMEN PERSEDIAAN (INVENTORY MANAGEMENT) PADA PT PURA MAYUNGAN - Tessa Handra (STIE Wiyatamandala, 2018)
Inventory management becomes very important aspect for manufactur firm in order to maintain lower cost of production. There is a model purposed by old management school that is called Economic Order Quantity to answer the question about how many stock that management need to order so could generate the lowest cost of production. Classical EOQ model has some challenge to be applied in the real practice of the firms. Firms prefer to order the component just base on the demand of the product montly as it more practical and easy to do. This research aim to applied classical EOQ in PT Pura Mayungan and analyze the efficiency of EOQ model. This research also compares EOQ computation and actual ordering method to find which model could generate lower cost for the firm. This research also using ANOVA to find the difference between total cost of inventory using actual data with total cost of inventory of EOQ. Finding of this research the saving of EOQ assumption is real. This research also suggest the firms could try to learn and adapt lean manufactur to create better value added.